Iron Starvation Conditions Upregulate Ehrlichia ruminantium Type IV Secretion System, tr1 Transcription Factor and map1 Genes Family through the Master Regulatory Protein ErxR - Moumène, Amal; Gonzalez-Rizzo, Silvina; Lefrançois, Thierry; Vachiéry, Nathalie; Meyer, Damien F. (Frontiers in Cellular and Infection Microbiology, 2018)
Ehrlichia ruminantium is an obligatory intracellular bacterium that causes heartwater, a fatal disease in ruminants. Due to its intracellular nature, E. ruminantium requires a set of specific virulence factors, such as the type IV secretion system (T4SS), and outer membrane proteins (Map proteins) in order to avoid and subvert the host’s immune response. Several studies have been conducted to understand the regulation of the T4SS or outer membrane proteins, in Ehrlichia, but no integrated approach has been used to understand the regulation of Ehrlichia pathogenicity determinants in response to environmental cues. Iron is known to be a key nutrient for bacterial growth both in the environment and within hosts. In this study, we experimentally demonstrated the regulation of virB, map1, and tr1 genes by the newly identified master regulator ErxR (for Ehrlichia ruminantium expression regulator). We also analysed the effect of iron depletion on the expression of erxR gene, tr1 transcription factor, T4SS and map1 genes clusters in E. ruminantium. We show that exposure of E. ruminantium to iron starvation induces erxR and subsequently tr1, virB and map1 genes. Our results reveal tight co-regulation of T4SS and map1 genes via the ErxR regulatory protein at the transcriptional level, and, for the first time link map genes to the virulence function sensu stricto, thereby advancing our understanding of Ehrlichia’s infection process. These results suggest that Ehrlichia is able to sense changes in iron concentrations in the environment and to regulate the expression of virulence factors accordingly.